Gulp [compact disc, unabridged] : adventures on the alimentary canal - Roach, Mary (Tantor Media, 2013)
Why is crunchy food so appealing? Why is it so hard to find words for flavors and smells? Why doesn't the stomach digest itself? How much can you eat before your stomach bursts? Can constipation kill you? Did it kill Elvis? In Gulp we meet scientists who tackle the questions no one else thinks of; or has the courage to ask.